Sejarah dan Perkembangan Kritik Matn Hadis - Irham, Masturi (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2011)
Prophet Muhammad recommends to us, the Muslims to always keep and save his Sunnah of alteration and forgery. In addition, the Prophet Muhammad also invited and called for his Sunnah preserved and passed on to others. Instead, the Prophet threatens those who lie on his behalf, also those who add and subtract, especially falsifying his hadith, criticism of honor becomes a necessity in the narration hadith. If at the present time, the researchers’ hadith criticism has been presented with the concept of honor that has been established, it is different from previous periods. Criticism of honor has a history that may not be forgotten and will always experience growth. Discussion on the issue will be reviewed in this article. The article also stated that the seriousness of the researchers’ tradition from generation to generation has never diminished, despite the criticism of the method used matn not exactly the same as before.